الحس الثوري في الشعر الموجه للطفل، الشاعر "جموعي أنفيف" أنموذجا - اقطي, نوال; مشقوق, هنية (جامعة الوادي - University of Eloued, 2021)
تروم هذه الدراسة الوقوف على البعد الثوري في شعر الأطفال، مع اختيار مدونة الشاعر الجزائري" جموعي أنفيف" الذي ركز على الثورة الجزائرية في كتابته للأطفال، مما يعبر عن إجلاله لهذا الحدث وتعظيمه للشهداء الأبرار. وتستعين بالمنهج الوصفي والاستقرائي، موظفة آلية الوصف والتحليل فاعلية إجرائية لعرض تجربة الشاعر النابضة بالحس الثوري، والبحث في خصوصية المكان. Abstract: This study aims at focusing on the revolutionary feeling within the children poetry with choosing the Algerian poet JmoueiAnfif’s corpora. The poet focuses on the Algerian revolution in his writings for the children, which indicates his respect to this event and glorifying the worthy righteous martyrs. This study follows the descriptive and the inductive methods with using description and analysis mechanisms as an operative effectiveness for browsing the poet’s experience, which is vibrant with the revolutionary feeling, and searching in the place specificity
مقال
Keywords: الحس الثوري، شعر الأطفال، المقاومة، المكان التاريخي، الهوية.